Tantangan Diagnosis Blefarokonjungtivitis: Sebuah Laporan Kasus Herpes Simpleks Okular - Amatul Shafi; Putri Frima Laviga Barus (International Medical Journal Corp. Ltd, 2025)
Introduction: Blepharoconjunctivitis presents a diagnostic challenge owing to its multifactorial etiology, with viral pathogens representing a significant subset of causative agents. HSV infection may affect all stuctures of the eye, including blepharitis. Establishing a right diagnosis is challenging, as HSV blepharitis is uncommon and may be confused with other eyelid disease manifestation. Repeated recurrences can result in serious ocular problem such as endothelial and stromal keratitis, which can induce permanent visual loss. Precise diagnosis is essential to avoid many of the vision-threatening complications associated with ocular HSV. Purpose: To highlight the challenges of diagnosing blepharokonjunctivitis, particularly when it presents as a mystifying case of ocular herpes simplex. Case Illustration: A 22-year-old female presented with sudden swelling of the right eyelid, accompanied by predominant pain and headache, and was initially diagnosed with a lacrimal system disorder. After treatment, the symptoms progressed, prompting a follow-up visit during which a thorough history was taken. Fine, whitish, confluent vesicles were observed on the upper and lower right eyelids, along with a linear lesion on the left side of the nasal bridge. Anterior segment seems clear and there was no conjunctival injection. The diagnosis was revised to ocular herpes simplex. Topical asiklovir therapy yielded a good clinical response. Conclusion: Timely identification of viral causes is essential for effective clinical management and for reducing the likelihood of related complications. Consequently, a comprehensive knowledge of the clinical features, epidemiological patterns, and diagnostic approaches is crucial for the precise diagnosis and appropriate management of viral blepharokonjunctivitis. Despite limitations in diagnostic resources, clinicians must sharpen their skills in history taking and basic physical examination, while also emphasizing the importance of patient adherence to follow-up care.